Unravelling the secretions of the silkworm. (1st March 2019) - Atkinson, Elizabeth Eleanor Jacqueline
This article will propose how the physical material of the silkworm might unsettle and entice us to consider an alternative means of relating to others. Examining work by the artists Kumi Oda and Candice Lin, this article will search for forms of relationships not based on the appropriation and exploitation of animal difference for the distinction and profit of the human species. Musing over both Haraway's and Derridean theories, the article will unravel the strangeness of silkworms, mingling more intimately with their physicality in efforts to stitch together a new ontology that accommodates the multiplicity of differences present and in emergence, within both the species of our own, and those of others.